2019
DOI: 10.3390/ijerph16111999
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Non-Emergent Visits in Emergency Departments: Profiles and Longitudinal Pattern Changes in Taiwan, 2000–2010

Abstract: An increasing number of emergency department (ED) visits have posed a challenge to health systems in many countries, but an understanding of non-emergent ED visits has remained limited and contentious. This retrospective study analyzed ED visits using three representative cohorts from routine data to explore the profiles and longitudinal pattern changes of non-emergent ED visits in Taiwan. Systematic-, personal-, and ED visit-level data were analyzed using a logistic regression model. Average marginal effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The rate of non-emergent ED visits (9.9%) was lower than those reported in previous studies which are between 4.8% and 90% [ 4 , 18 , 19 ]. Although the rates of ED use vary by country and region due to these different definitions, some factors such as socioeconomic conditions, hospital admission policy, private health insurance coverage, personal health system utilization, and chronic disease profile of the population have been shown to drive geographical variation in ED visits [ 4 , 20 , 21 ]. The most challenging part of these studies was determining non-emergent ED visits, which were largely estimated, relying on diagnostic criteria or the judgment of clinical staff in previous studies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of non-emergent ED visits (9.9%) was lower than those reported in previous studies which are between 4.8% and 90% [ 4 , 18 , 19 ]. Although the rates of ED use vary by country and region due to these different definitions, some factors such as socioeconomic conditions, hospital admission policy, private health insurance coverage, personal health system utilization, and chronic disease profile of the population have been shown to drive geographical variation in ED visits [ 4 , 20 , 21 ]. The most challenging part of these studies was determining non-emergent ED visits, which were largely estimated, relying on diagnostic criteria or the judgment of clinical staff in previous studies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unnecessary ED visits, which are defined as ED visits amenable to intervention by ambulatory care due to low acuity (LA), 19 20 have been analysed to estimate inefficiency or waste in emergency care systems. 2 4 14 21 Since the 1990s, several studies have conducted investigations into preventable ED visits. 19 20 22 The concerns regarding adverse consequences of LA visits are that LA ED visits may worsen ED overcrowding; thus affecting the quality of ED care, 23 24 and adding to the inefficiency in healthcare delivery by levying excessive cost on health systems.…”
Section: Introductionmentioning
confidence: 99%
“… 20 24 Studies have revealed an increasing trend of ED utilisation in many countries with different healthcare systems, 4 5 14 21 25 26 but only a few have investigated changes in LA ED over time. 2 11 27 Although single-centre and multi-centre studies have estimated that 20%–65% of paediatric ED (PED) visits are likely to be classified as LA, 2 15 28 29 none of these studies specifically focused on the changes in LA PED visits in the paediatric population over time. The paediatric population is the main user of ED services 27 and a main contributor to LA ED visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ed is always convenient providing nonstop care by trained specialized team. According to some studies; it has been proved that a higher rate of nonemergency application is noticed in case of unavailability of primary health care centers access and during off-clinic hours [2]. The delayed appointments, and the lack of access to outpatient clinics on evenings and weekends is usually influencing the patient's attitude.…”
mentioning
confidence: 99%